Simbolos de consumo. Consumo de símbolos. Robert Venturi e Denise Scott Brown - Marcos Quintino Gonçalves Maia (2012)
This work deals with the role of architecture in consumer society based on the work of Robert Venturi and Denise Scott Brown. In this sense, the archeology and context of the architects' theoretical construction is approached through the analysis of three topics connected, respectively, with the study of the artistic object, the relation with mass culture and the influence of consumption in architecture. In the first one, the concept of poetry developed by Robert Venturi in the early years of his career, strongly influenced by literary criticism, will be approached. This concept will be preponderant in his creative process and the way he sees the architecture from the past and present. The recognition of the presence of the past in the artist's work marked the relationship of the architect with History, while the ontological study of the poem introduced the concepts of contradiction, ambiguity and dramatism in his speech. The second topic deals with the relationship with popular culture, recognizing the role of Denise Scott Brown in this new dimension of Venturi's theory. The influence of Pop artists and sociology in the acceptance of the ordinary and the search for more tolerant methods of analysis and intervention allowed the architects to learn from Las Vegas and Levittown. The acknowledgment of the convencional element as a symbol and instrument of architectural communication has changed the relationship between the architecture of the authors and the public. While the irony and the decontextualization became useful tools to associate new meanings to popular vocabularies. Finally, the influence of consumer society becomes clear in the authors' recommendation for a monument and the recommendations for urban planning. The reference to the decorated shed, detaching structure and symbol, reflects the anatomy of the consumption object and the role of media in the split between use and image. The concept of urban iconography and monumentality reflects the influence of cultural relativism and the power of the symbols in the context of the city. The relationship of Venturi and Scott Brown with the work of his contemporaries allows the understanding of the authors' view of the architecture's media coverage and the resulting dissemination of images and theories.